Efficiency of Gryon fulviventris (Hymenoptera: Scelionidae) as an egg parasitoid of Clavigralla tomentosicollis Stal. (Hemiptera: Coreidae) in northern Nigeria - Asante, Stephen K.; Jackai, L.E.N.; Tamo, Manuele (Oxford University Press, 2000)
Field surveys were conducted on cowpea and pigeon pea in 1995 and 1996 to assess the effect of indigenous egg parasitoids on populations of Clavigralla tomentosicollis Stål in northern Nigeria. From the egg masses of C. tomentosicollis, three species of Hymenoptera belonging to three families, namel Anastatus sp. (Eupelmidae), Ooencyrtus utetheisae (Risbec) (Encyrtidae), and Gryon fulviventris (Crawford) (Scelionidae), were recorded. Among them, G. fulviventris was found to be the most abundant parasitoid. Of a total of 3,502 egg masses collected on cowpea from four geographical locations, 2,587 (73.9%) were found to contain at least one egg parasitized by G. fulviventris. From 56,072 eggs discovered, it parasitized 38,935 (69.4%). Overall, 74,724 eggs were collected from the four different locations and of these 52% were parasitized by G. fulviventris. However, parasitism rates varied with time and location. At one of the study sites (Minjibir, Kano) where weekly samples were collected throughout the growing season, the discovery efficiency, exploitation efficiency, and overall percentage parasitism increased significantly from July to November. Also, the proportion of eggs parasitized was found to be inversely related to the size of the egg mass. These findings are discussed in relation to the potential contribution of biological control in the integrated pest management of this economically important pest.